Crisis of shared affect in human-animal relationship in Philip K. Dick’s Do androids dream of electric sheep? - Sharma, Prakash; Baral, Pabitra Raj (Nepal Journal of Multidisciplinary Research, 2024)
Background: Philip K. Dick’s novel Do Androids Dream of Electric Sheep? critiques humanity's failure to achieve intersubjective transformation and highlights the breakdown of shared emotional connections. The narrative delves into human characters’ obsession with owning pets, revealing their motivations as less empathetic and more rooted in reinforcing human centralism. Objective: This study investigates the human-animal relationship and human characters’ fixation with animals in the novel, employing posthumanist perspectives to explore interspecies relationality and the concept of companion species. Methods: The study employs a qualitative research design and textual analysis method to examine the primary text. It draws theoretical insights from posthumanism, particularly the works of Donna Haraway and other leading scholars on interspecies relationality. Secondary sources, including books, journal articles, and critical reviews, are utilized to scrutinize the crisis of affect in human-nonhuman interactions. Findings: The analysis reveals that human characters in the novel aspire to keep animals primarily out of social obligation and moral duty. However, their motivations lack genuine emotional connection, underscoring a crisis of affect in their interactions with nonhuman beings. Conclusion: The study concludes that the human-animal relationship depicted in the novel reflects a superficial and obligation-driven dynamic, failing to achieve authentic interspecies relationality. Novelty: This research contributes to the study of human-animal relationships and interdependence by offering a posthumanist critique of affect and interspecies relationality in Do Androids Dream of Electric Sheep?.